Case report: Genetic diagnoses in a pediatric patient with retinoblastoma and comorbid global developmental delay: three distinct entities diagnosed by whole exome sequencing in a single patient - Chen, Jing; Yang, Shuo; Wang, He; Wang, Hongjing; Xiao, Yuanyuan; Liu, Shanling (Frontiers in Neuroscience, 2024)
Background The objective of this study was to explore the genetic etiology and propose a genetic diagnosis and counseling strategy for children with retinoblastoma (RB) and global developmental delay (GDD). Case presentation We report on a 2 years and 4 months old boy with binocular retinoblastoma and global developmental delay (included intellectual disability, language development delay, motor development delay, etc.). Genomic DNA was extracted from peripheral blood mononuclear cells isolated from the proband and his parents. Whole exome sequencing (WES) was carried out for the proband and his parents to identify genetic etiology, which was subsequently verified by quantitative polymerase chain reaction (qPCR).The WES revealed a gross heterozygous deletion in the RB transcriptional corepressor 1 (RB1, OMIM:614041) gene, including exon 7–8, in the affected proband but not in his parents. Additionally, two pathogenic copy number variations (CNVs) were identified: a duplication at 7q11.23 and a microdeletion at 16p11.2-p12.2, respectively. Furthermore, the genomic qPCR analysis demonstrated a 50% reduction in the copy numbers of exon 7 and exon 8 in the RB1 gene of the proband, as compared to those detected in his parents. Simultaneous variants in the RB1 gene and two pathogenic CNVs can precisely explain the genetic etiology of the proband. Conclusion The present study firstly reports a novel gross deletion variant of the RB1 gene coexisting with two pathogenic CNVs in a pediatric patient with retinoblastoma and comorbid global developmental delay in China. Additionally, our findings strongly support the use of WES in pediatric patients with RB comorbid GDD, and WES is recommended as the first-tier test.